Design And Construction of a Mobile Dust Catch Using Wet Scrubber Technology in a Wood Factory - Achmad Hilal Rusydi; Denny Dermawan; Wiwik Dwi Pratiwi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The wood processing industry is a significant source of airborne dust emissions and wastewater, both of which can pose serious environmental and health hazards if not properly managed. This study aims to evaluate the performance of a mobile dust collection system utilizing wet scrubber technology at two primary operational points—cutting and sanding—while also assessing the effectiveness of treating dust-laden wastewater using electrocoagulation. The system was designed with a 55-liter tank and equipped with eight electrode plates (four aluminum and four iron) measuring 20 × 25 cm, providing a total effective area of 0.8 m². Experimental results demonstrated that the initial Total Suspended Solids (TSS) concentration of 440 mg/L was reduced to 250.55 mg/L after electrocoagulation, and further to 189.45 mg/L after filtration. Additionally, the addition of 200 mg/L of Poly Aluminium Chloride (PAC) reduced TSS from 320 mg/L to 40 mg/L, achieving an 87.5% removal efficiency. Field tests showed that the system successfully reduced airborne particle concentrations by 69.6% in the cutting area and 26.24% in the sanding area. These findings indicate that the proposed mobile wet scrubber system is effective in reducing both airborne dust and TSS levels in wastewater, making it a viable solution for dust control in wood processing industries.